Technology Entreprenurship in the Changing Business Environment – A Triple Helix Performance Model - Maja Levi Jaksić; Milica Jovanović; Jasna Petković (Amfiteatru Economic)
In this paper the contribution of technology management and entrepreneurship to sustainable development is emphasized and the Triple Helix (TH) model is used to analyse the performance of different actors in accomplishing the activities of Technology Innovation Management and Entrepreneurship (TIME). By analysing TH model (Government – University – Industry) in relation to accomplishing TIME main functions: Planning, Organizing and Control (POC), we created a general model which measures TIME effectiveness related to the key elements of the TH model. The general model – TMD-TH (Technology Management and Development – Triple Helix) represents the framework for further more specific research into the relations of the observed dimensions. From the general model, three sub-models are excluded: TMD-G (Government), TMD-U (University) and TMD-I (Industry), and each of TH dimensions is observed by a set of indicators classified from the perspective of the specific function (POC) of TIME. This provides better categorization of TIME indicators and linkage with the actors in the TH model. The applicability of the suggested general model was tested by a set of indicators at the example of Serbia, Austria and Finland and comparison of these countries was made from a perspective of innovativeness and sustainable development. Since technology, innovation and entrepreneurship are considered as the main forces leading to sustainable development at different levels of the economy and society, it is of paramount importance to develop our capacities to better monitor, analyse and develop these forces. A model is developed with a set of indicators that enables the systematic analysis in concrete situations in practice. In this paper, the model is applied at the level of the national economy, the results obtained point to the most critical activities of the actors in the TH model in accomplishing TIME. The performance model represents a base for developing policies and strategy better tuned to the urgent needs of the economy and society in developing TIME directly related to accomplishing a higher level of sustainable development.